Prevalence and genetic diversity of optrA-positive enterococci isolated from patients in an anorectal surgery ward of a Chinese hospital - Li, Yuanyuan; Jiang, Tao; Mao, Jianfeng; Xu, Fangyi; Zhang, Rong; Yan, Jing; Cai, Jiachang; Xie, Yanjun (Frontiers in Microbiology, 2024)
Linezolid-resistant enterococci has increased in recent years due to worldwide spread of acquired resistance genes (cfr, optrA, and poxtA) in clinical, animal, and environmental settings. This study investigated the carriage of optrA-positive enterococci among patients in the anorectal surgery ward in Hangzhou, China, and characterized the genetic context of optrA. A total of 173 wound secretion samples were obtained to screen optrA-positive enterococci. Of the 173 samples, 15 (8.67%) were positive for optrA, including 12 Enterococcus faecalis, two E. faecium, and one E.hirae. Multilocus sequence type analysis revealed that 12 optrA-positive E. faecalis isolates belonged to eight different sequence types (STs), of which ST16 was the main type. Eight OptrA variants were identified, whose optrA flanking regions with a fexA gene downstream were bounded by different mobile genetic element. Furthermore, the optrA gene in eight out of fifteen optrA-positive enterococci could be successfully transferred through conjugation. The findings revealed a high carriage rate of optrA in enterococci from one anorectal surgery ward in China. The dissemination of optrApositive enterococci isolates in clinical settings should be continually monitored.